Strategi Bauran Pemasaran Dalam Meningkatkan Volume Penjualan Corporate Events Di PT. Bali Multi Sarana - Diaz, Christina Audrey Amandarani; Kusumarini, Indah; Asmarani, I Gusti Ayu Ratih (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
This research is a qualitative descriptive study. The purpose of this study was to determine the marketing mix strategy at PT. Bali Multi Sarana in an effort to increase the sales volume of corporate events. Data was collected through interviews, observation and documentation studies. The data analysis technique used is SWOT analysis and the 7P marketing mix (price, product, place, promotion, process, people and physical evidence). Based on the results of data analysis, it is known that there are four marketing mix strategies to increase sales volume of corporate events at PT. Bali Multi Sarana, SO strategy (Strength Opportunity) to maximize corporate events and marketing services through social media, build networking with the venue. ST strategy (Strength Threats) highlights the advantages of corporate events and equipment products, makes attractive promos and displays client testimonials that have used the company's services on social media. WO strategy (Weakness Opportunity) is to recruit marketing staff, make sales calls, utilize networking with old clients. WT strategy (Weakness Threats) maximizes promotions regarding the advantages of corporate events products and conducts research on competitors in conducting marketing.